ESP Students’ Preferences in Learning English: Face to Face Corrective Feedback vs Online Corrective Feedback - Nurizzi Rifqi Ferdian (English Education Department at FKIP Nommensen University, 2020)
ABSTRACT The current study aims to explore the students’ preferences on face to face corrective feedback vs online corrective feedback in ESP class. It is an attempt to investigate if they prefer to be corrected directly face to face by teachers or they like to be provided online corrective feedback by the teachers. To do so, a questionnaire was distributed to a group of students who are taking English for Specific Purposes and also focus group discussion was used in order to find out their beliefs toward their corrective feedback preferences. Totally, 50 students who were taking ESP courses at State Polytechnic of Subang participated in this study. The results from the questionnaire analysis revealed that the students preferred their teachers to use face to face corrective feedback, with an overall mean (x̄ = 3,95) in learning effectiveness, (x̄ = 4,12) in learning accuracies, and (x̄ = 4,02) in learning experiences. The focus group discussion revealed the students’ beliefs in their corrective feedback preferences, they believed that the teachers should be able to guide their learning, use communicative ways, and encourage them by using their learning preferences. The study suggested that taking these preferences into consideration could help students to increase their confidence in learning English. Keywords: Corrective Feedback, Face to face, Online, English Learning